PEDAGOGICAL AND PSYCHOLOGICAL ASPECTS OF DEVELOPING CREATIVE QUALITIES IN STUDENTS IN GENERAL SECONDARY SCHOOLS - Kasimova Charos; Yarmanova Yulduz Burievna (American Journals, 2025)
This article presents information about the importance of developing creative qualities in students, as well as views and theories on the organization of individual creative activity. Special attention is also paid to the qualities of creative people.
Keywords: Creative, creativity, personality, approach, education, students, creativity, formation, quality, creative approach.